Pengaruh Latar Belakang Pendidikan, Usia, Peredaran Usaha, Lama Usaha, Dan Pemahaman Pengusaha UMKM Terhadap Tingkat Kepatuhan Pemenuhan Kewajiban Perpajakan - Anastasia Rachmawati; Vita Aprilina (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
The purpose of this research is to analyze the influence of educational background, age, business circulation, length of business, and understanding of entrepreneurs of UMKM in Bekasi to the level of compliance fulfillment of tax obligations. The research method used quantitative research method. The study was conducted to entrepreneurs of UMKM in Bekasi with a total of 291 total population in 2016. The sample of this research is 78 respondents of UMKM entrepreneurs in Bekasi. With sampling technique using Slovin formula. The analytical method used is multiple linear regression. The results obtained by the authors in this study indicate that educational background and understanding of UMKM entrepreneurs have a positive and significant impact on the level of compliance fulfillment of tax obligations of UMKM entrepreneurs in Bekasi. While the age, business circulation, and length of business do not affect the level of compliance fulfillment of tax obligations of UMKM entrepreneurs in Bekasi